PENGARUH MEDIA POWERPOINT INTERAKTIF BERBANTU CANVA TERHADAP KEAKTIFAN BELAJAR SISWA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 182 PEKANBARU - Saputri, Yona; Siti Quratul Ain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research aims to determine the effect of interactive PowerPoint media assisted by Canva on students' active learning in Pancasila education subjects in class IV SDN 182 Pekanbaru. The research sample consisted of thirty-one class IV students at SDN 182 Pekanbaru. The type of research used in this research is quantitative research. The analytical method used in this research is simple linear regression analysis using SPSS for Windows 22 for data processing. The findings show that the use of PowerPoint media has an influence on the active learning of students in Pancasila Education Class IV Sdn 182 Pekanbaru. This is indicated by a significance value of 0.029, meaning that the magnitude of  < 0.05 causes H0 to be rejected and H1 to be accepted. This means that the better the use of PowerPoint media used by the teacher, the better the student's learning activity will be. Based on the R Square (R2) value, it can be said that student learning activity is influenced by the variable use of PowerPoint media by 39.2%. The other 51.8% was influenced by variables that were not explained or studied in this study.